The Prognostic Value of PERK in Cancer and Its Relationship With Immune Cell Infiltration - Wang, Peng; Han, Liying; Yu, Moxin; Cao, Zhengyu; Li, Xiaoning; Shao, Yunxia; Zhu, Guoping (Frontiers in Molecular Biosciences, 2021)
Background: PERK is a type I transmembrane protein that functions as an endoplasmic reticulum (ER) stress sensor to regulate global protein synthesis. Recent researches suggest that PERK, as important receptor protein of unfolded protein response, is involved in the pathogenesis of many cancers. This study aimed to investigate the PERK expression and its relationship with the prognosis in the Pan-cancer, and attempted to explore the relevant mechanism of PERK involved in the regulation of cancer pathogenesis. Methods: The Oncomine database and TIMER database were used to analyze the expression of PERK between the Pan-cancer samples and normal samples. The survival analysis was performed by PrognoScan database, Kaplan-Meier (K-M) plotter database and UALCAN database. The Gene Set Enrichment Analysis (GSEA) was used to perform the functional enrichment analysis of PERK gene in BRCA, HNSC and THCA. The TIMER database was used to investigate the correlation between the PERK expression and tumor infiltrating immune cells and analyze the relationship of PERK with marker genes of immune cells which were downloaded from the CellMarker database in BRCA, HNSC and THCA. Results: PERK was differentially expressed in various cancers, such as breast cancer, liver cancer, lung cancer, gastric carcinoma, lymphoma, thyroid cancer, leukemia and head and neck squamous cell carcinomas. The high-expression of PERK was associated with a poor prognosis in KIRP, LGG, BRCA and THCA, and with a favorable prognosis in HNSC. The results of GSEA indicated that PERK was mainly enriched in the immune-related signaling pathways in BRCA, HNSC, and THCA. Moreover, PERK expression was significant positively correlated with infiltrating levels of macrophages and dendritic cells, and was strongly associated with a variety of immune markers, especially macrophage mannose receptor 1 (MRC1, also called CD206) and T-helper cells (Th). Conclusion: High expression of PERK could promote the infiltration of multiple immune cells in the tumor microenvironment and deteriorate outcomes of patients with breast and thyroid cancers, suggesting that PERK could be taken as a potential biomarker of prognosis and tumor-infiltrating immune cells.